Caracterização e potencial de comércio da carne de capivara criada em sistema semi-intensivo - Cunha, Waldeliza Fernandes da (2014)
The objective of this study was to evaluate efficiency, profitability and quality of housing, físicos- chemical parameters and acceptability of capybara meat grown in semi-intensive system, as well as knowing the profile and beliefs of consumers of exotic meat. The thesis is composed of five chapters, the chapter 1, initial considerations that addresses the motivations of research and so on and finally concludes as all, as this is the thesis summary. We conducted a literature review on the topic, from biology and habits of the capybara, the market of wild animals and meat quality. Subsequently characterized the carcass and cuts capybara as income, profitability and microbiology. For this, we used six coming adult capybaras (76kg) the commercial breeding of Jatai GO, slaughtered in the experimental abattoir IF Goiás Campus Ceres. The results showed hot carcass dressing (WHR) in relation to body weight (BW) of 52,9%. The yields of retail cuts (RCC) in descending order were: ham and (31,33%), shoulder (26,67%), rib (17,33%) and loin (10,67%), the profitability of housing is incremented when the cuts are marketed separately, there was no contamination by Salmonella. The physicochemical analyzes, we evaluated the proximate composition, water holding capacity (WHC), shear force (FC) and the color, the cuts from the loin, shank and the palette of six capybaras were used. The results showed that capybara meat has low levels in relation to Domestic meat lipids, highlighting the palette. There was no difference between the cuts for the CRA, HR ranged from 5,3 to 7,1, indicating softness. For color, the palette contents were lower in red (a *) for revealing lower lipid contents. Assessing the acceptability of capybara meat cuts and types of crackling, offering up different types of meat to consumers. The results showed that the capybara meat had similar acceptance pork and lamb, being lower than the beef. To know the profile and beliefs of consumers (end and distributors) of these products in the towns of Caldas Novas, Ceres and Goiânia, GO . The results showed that respondents consume meat of any wild form, capybara meat is the most consumed in the form of meatballs. It was evident that even family and friends influenced the consumption of these products. Finally, we observed the existence of belief that meat from animals raised in captivity is healthier, attributing the quality, price and availability of the product as determinants of increased consumption of meat of wild animals in these regions studied. We conclude that capybara meat has the potential consumer and marketing.